Edukasi Mengenai Penyakit Zoonosis Dan Pencegahannya Di Desa Pasar X Dusun III Kecamatan Kutalimbaru - Saputri, Hera Octavia; Rahman, Shahrul (Jurnal Ilmiah Wahana Pendidikan, 2025)
Zoonotic diseases, which are transmitted between animals and humans, pose a significant health risk, especially in rural areas where interactions between humans and animals are frequent. This study focuses on an educational initiative aimed at raising awareness of zoonotic diseases in Pasar X Village, Kutalimbaru Sub-district, which is a community with limited knowledge of these diseases. This community-based education program used visual aids such as posters and engaged participants through interactive discussions. Findings showed that the education program successfully increased community knowledge and awareness of zoonotic disease risks and prevention measures. Although participants initially had limited understanding, the interactive educational approach and use of visual media proved effective in clarifying the information. However, several challenges such as communication barriers and limited resources still hamper the implementation of preventive measures in the field. Overall, this study emphasizes the importance of sustainable and adaptive health education to reduce the risk of zoonotic transmission in rural areas.